CHARGE-TRANSFER COMPLEXES OF CHLORPHENOXAMINE HYDROCHLORIDE WITH CHLORANILIC ACID, 2,3-DICHLORO-5,6-DICYANO-1,4-BENZOQUINONE AND 7,7,8,8-TETRACYANOQUINODIMETHANE AS π-ACCEPTORS - EL-DIDAMONY, AKRAM M.; SAAD, MOUNIR Z.; RAMADAN, GEHAD M. (International Journal of Applied Pharmaceutics, 2019)
Objective: To develop simplified, accurate and precise visible spectrophotometric strategies for the assay of chlorphenoxamine hydrochloride (CPX) in pure drug and in its pharmaceutical preparations. Methods: The described methods depended on the formation of charge-transfer (CT) complexes of intense color between CPX as donor with three π-acceptors, chloranilic acid (CLA), 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), and 7,7,8,8-tetracyanoquinodimethane (TCNQ) and the colored reaction products were estimated spectrophotometrically at 520 nm, 460 nm and 840 nm for CLA, DDQ, and TCNQ complexes, individually. All the optimum conditions were established. The proposed methods were validated in term of linearity, limit of detection as per the international conference on harmonization guidelines ICH Q2 (R1). Results: The complexes obeyed Beer’s law in the concentration range of 16-144, 6-54 and 4-76 μg/mlwith molar absorptivity at 0.30×104, 0.68×104 and 0.58×104 l/mol/cm for CLA, DDQ, and TCNQ, individually. According to Benesi-Hildebrand plots, the association constants and changes of standard free energy were determined. 1:1 was the ratio of composition of the formed CT-complex. Conclusion: The obtained results revealed that the developed method can be applied successfully for the determination of CPX in drug formulations samples with good accuracy and precision.